ECONOMIC VIEWS OF THE FIRST RENAISSANCE THINKERS (BASED ON THE ECONOMIC OUTLOOK OF ABU NASR FARABI AND YUSUF KHOS KHAJIB) (Web of Teachers: Inderscience Research, 2024)
This article presents the organizational, economic and legal factors of management, property relations, distribution process, satisfaction of people's needs, agrarian sector and land ownership in the economic outlook of Abdu Nasr Farobi and Yusuf Khos Khajib, the bright representatives of the first renaissance.